Productive Landscapes Project. Report of the First Season (Nov-Dec 2014). (November 2015) - Zerbini, Andrea
Abstract : The Productive Landscapes Project (PLP) was launched in 2014 with the aim of studying the ancient wine- and oil-producing infrastructure of north-west Jordan. The survey region, which comprises ca. 2, 000 km 2 from the Yarmouk to the Zarqa river, and from the Ghor to the west to the wadi Shellaleh to the east, was among the most densely inhabited of the southern Levant, boasting in the Roman and Byzantine period some of the largest urban settlements of the region. PLP is a GIS and survey project which aims to record and study all of the wine and oil-producing sites within the study region with the goal of establishing technological typologies, estimating production capacities and, ultimately, chronology. During the first season, 186 sites were entered in the GIS of the project, and 67 of them were ground-checked. Ten new sites were discovered through chance discovery during fieldwork. A preliminary typology of four types of presses was established, with a technological portfolio closely mirroring those of neighbouring Galilee, the Golan and Lebanon. As far as production capacity is concerned, the vast majority of installations appear to have catered for household needs. However, a number of sites, mostly associated with churches and monasteries, were clearly designed to process a marketable surplus.